2010
DOI: 10.1103/physreve.82.051404
|View full text |Cite
|
Sign up to set email alerts
|

Free energies, vacancy concentrations, and density distribution anisotropies in hard-sphere crystals: A combined density functional and simulation study

Abstract: We perform a comparative study of the free energies and the density distributions in hard-sphere crystals using Monte Carlo simulations and density functional theory ͑employing Fundamental Measure functionals͒. Using a recently introduced technique ͓T. Schilling and F. Schmid, J. Chem. Phys. 131, 231102 ͑2009͔͒ we obtain crystal free energies to a high precision. The free energies from fundamental measure theory are in good agreement with the simulation results and demonstrate the applicability of these functi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
117
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(125 citation statements)
references
References 68 publications
7
117
1
Order By: Relevance
“…The Onsager approximation is valid at low densities reproducing the second virial coefficient of the bulk fluid equation of state correctly but is expected to break down at higher densities. Unfortunately, unlike for hard-core interactions 58,59 , no alternative approximation working at higher densities is known for soft inverse-power-law potentials 60 . However, we expect the general trends to be captured by the theory but not the details of molecular layering.…”
Section: Density Functional Theorymentioning
confidence: 99%
“…The Onsager approximation is valid at low densities reproducing the second virial coefficient of the bulk fluid equation of state correctly but is expected to break down at higher densities. Unfortunately, unlike for hard-core interactions 58,59 , no alternative approximation working at higher densities is known for soft inverse-power-law potentials 60 . However, we expect the general trends to be captured by the theory but not the details of molecular layering.…”
Section: Density Functional Theorymentioning
confidence: 99%
“…19, we start by fixing the packing fraction η r of the reservoir. In a defect-free two-dimensional solid with hexagonal order there would be N = 2 particles per unit cell.…”
mentioning
confidence: 99%
“…However, furthermore it was found: Z(i) No free energy minimum for n vac > 0 and (ii) equal free energies for fcc and hcp. In a study combining simulation and free minimization of FMT functionals [18] it was shown that (i)…”
Section: Introductionmentioning
confidence: 99%